KNOWLEDGE AND ATTITUDE OF FEMALE STUDENTS IN CERVICS CANCER PREVENTION - Suryanda Suryanda; Nelly Rustiati; Aisyah Aisyah (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
Cervical cancer is one of the main causes of death in women, especially in developing countries. It is important to take preventive measures early on in cervical cancer because adolescence is a period of long-term health knowledge, attitudes, and behavior formation. Without early education, prevention efforts are often delayed, namely increasing knowledge and forming positive attitudes among adolescents. This study aims to explore the relationship between the knowledge and attitudes of female students at SMAN 1 Prabumulih City regarding cervical cancer prevention efforts. The study applied a quantitative design with a descriptive analytical approach. The population of female students at SMAN 1 Prabumulih City amounted to 213 respondents and a purposive sampling sample of 138 people. Data were obtained through questionnaires, analyzed univariately and bivariately using Chi-Square tests. The findings of this study indicate that the majority of respondents have a level of knowledge that is classified as sufficient to good, and attitudes tend to be positive towards cervical cancer prevention efforts. Bivariate analysis showed a significant relationship between female students' knowledge and attitudes in preventing cervical cancer, with a p-value of 0.00 and a Contingency Coefficient (CC) value of 0.609, indicating a strong relationship. Although the Contingency Coefficient only assesses strength without clearly indicating direction, in the context of health knowledge and attitudes, it suggests that the better students' understanding (e.g., regarding risk factors, symptoms, and the HPV vaccine), the more favorable their attitudes toward preventive measures (e.g., willingness to be screened or vaccinated). There is a significant relationship between students' knowledge and attitudes toward cervical cancer prevention efforts. The better their knowledge, the more positive their attitudes.